(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the nutritional and rheological quality of ora-pro-nobis flour (OPNF) and its influence on the replacement of wheat flour (WF), through the analysis of physicochemical parameters, determination of phenolic compounds, antioxidant activity and rheological analyzes of wheat flour and mixtures with 10 to 30% OPNF. Flour blends with 10%, 20% and 30% of OPNF in substitution of WF in flour base were evaluated. The OPNF showed higher values of lipids (2.87%), proteins (18.29%), fibers (44.13%), ash (11.19%), minerals (Ca, Mg, K, Na, Fe and Zn), beta-carotene (71.37 µg 100 g-1), lycopene (25.02 µg 100 g-1), total chlorophyll (24.40 µg 100 g-1), ABTS radical-scavenging capacity (15.02 μmol Trolox eq. g-1) and DPPH (IC 50 = 33.30 μmol mL-1 extract) in relation to WF. The flour blends with 10%, 20% and 30% of OPNF showed a higher nutritional value and antioxidant activity proportional to the increase on OPNF concentration. The increasing on the concentration of OPNF in flour blends reduced the values of the gluten strength (P), tenacity (W), extensibility (L), water absorption and falling number. Moreover, it increased the values of dough development time, dough stability and water absorption. The results of rheological analyzes indicate that flour blends of OPNF (10%, 20% and 30%) with WF have characteristics suitable for use in biscuits, baked cakes and breads. The data from this study demonstrate the nutritional value and technological potential of OPNF for the development of food products.